The mediating effect of psychological capital on the relationship of entrepreneurial intention among hospitality undergraduates / Nur Azah Farhana Mohamed Fadzil , Zatul Iffah Mohd Fuza and Wan Nor Bayah Wan Kamarudin - Mohamed Fadzil, Nur Azah Farhana; Mohd Fuza, Zatul Iffah; Wan Kamarudin, Wan Nor Bayah (Universiti Teknologi MARA Cawangan Sarawak, 2022)
Entrepreneurial intentions require not only a strong desire, which is manifested through a positive attitude towards entrepreneurship but also a strong personal attribute to start a new business through an increase in psychological capital. This study investigates the mediation effect of Psychological Capital on the relationship of Entrepreneurial Intention among hospitality undergraduates. A quantitative study was implemented via an online survey in five (5) Malaysia’s Public Higher Education Institutions which resulted in a final sample of 297 undergraduates. Partial Least Squares-Structural Equation Modelling (PLS-SEM) software was used to analyse the data obtained using probability sampling. The results of this study indicate that the dimensions of psychological capital (hope, self-efficacy, optimism, and resilience) have a significant influence as mediating factors on entrepreneurial intention. In conclusion, as psychological capital is the positive psychological development of an individual, education providers should ensure that undergraduates obtain the necessary attributes as well as skills to function effectively.